Desenvolvimento de uma plataforma WEB para cálculos de dimensionamentos e verificações de estruturas metálicas conforme normas técnicas brasileiras: desenvolvimento de uma plataforma de cálculos WEB - Silva, Ronny Sousa (2021)
This work approaches the application of a programming method in a WEB platform’s development for calculations and sizing of metallic profiles and metallic structures according to the NBR 8800-2008 (Project Steel Structures of Steel and of Composite Structures of Steel and Concrete of Buildings), among others technical standards that are together. The design is subdivided according to the force application’s condition and loads suffered: Traction, compression, bending and torsion. The current way of programming is increasingly applied to 4.0 industry and cloud computing, through WEB calculation platforms. Thus, there is a need to reduce the time spent with sizing profiles, structural verification, monitoring of the calculation memorials generated and the used system visualization. The developed platform will follow, at this moment, the parts’ sizing in Traction and Compression, the application of some concepts of Strength of Materials that are most used and previous knowledge. The WEB platform RSSteel Online Calculation Platform was be developed using a Visual Studio Code source code editor in which was programmed using HTML 5, Javascript (ecmasCRIPT 2021) and CSS 3 to compose the entire system’s front-end and PHP 5.6 for the back-end, as well as MySQL to work the system's database, being useful to user registration, user differentiation, access levels and possibility of saving developed works. For the development of the front-end’s support, the Bootstrap 4.6 framework was used for design and direct visualization in the user-platform iteration. The result obtained was satisfactory with an objective, intuitive and responsive WEB platform being presented to the target audience and obtaining approval from users